The Change of Sales Modes in International Markets: Empirical Results for German and British High-Tech Firms - Helmut Fryges (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
The choice of the appropriate sales mode belongs to the firm?s most important strategic decisions after entering into a foreign market. Thus, it is important that the selected foreign sales mode best suits a firm?s available resources and capabilities. However, these resources and capabilities change over time. Therefore, it might be necessary for a firm to adjust its foreign sales mode to these changing firm-specific conditions. Using a longitudinal data set of newly founded technology-based firms in Germany and the UK, this paper applies logistic regressions and analyses empirically the probabilities of changing between the two sales modes most frequently used by the sampled exporters: direct exports and exporting via an intermediary. The estimation results confirm the importance of the firm?s physical and intangible resources as well as the influence of transaction-specific assets on a sales mode change. However, the effects of the latter factors might be dominated by strategic considerations that are not covered by our data. For example, a young high-tech firm will resort to an intermediary regardless of its resources and transaction-specific assets if this is the only way of coming into contact with foreign customers.
Keywords: L60; F23; L86; 330; High technology industries; internationalisation; sales modes; Vertriebsweg; Export; Internationale Markteintrittsstrategie; Unternehmensentwicklung; Hochtechnologiesektor; Schätzung; Deutschland; Großbritannien